Vagus nerve stimulation for the treatment of depression. - Panescu, D.
Given the debilitating effects of chronic depression and its economic impact on medical care, there is a need for a well-tolerated and effective long-term treatment for patients who do not respond fully to first-line antidepressant therapies such as antidepressant drugs (ADD), psychotherapy and electroconvulsive therapy. This paper discusses a new treatment that can address this need - the vagus nerve stimulation (VNS) therapy system - an implantable device that can electrically pace the vagus nerve. The VNS technology consists of a pulse generator and a lead system. In the VNS system, just like in a cardiac pacemaker, the stimulator resides subcutaneously and sends an electrical pulse to an organ through an implanted electrode. The VNS pulse generator is a programmable bipolar stimulator. The VNS lead system comprises a bipolar electrode pair and a fixation anchor that are wrapped around the left vagus nerve in the neck, near the carotid artery. The clinical safety and effectiveness of the VNS system was assessed. At present, the VNS therapy system can now be used as treatment for chronic or recurrent depression for patients 18 years of age or older who are experiencing a major depressive episode. The system can only be used as adjunctive therapy, which means that patients still need to continue with their ADD medication.
Keywords: Adjunctive therapy; Antidepressant drugs; Bipolar electrode pair; Carotid artery; Chronic depression; Electrical pacing; Electrical pulse; Electroconvulsive therapy; Fixation anchor; Implantable device; Implanted electrode; Lead system; Organ; Programmable bipolar stimulator; Psychotherapy; Pulse generator; Vagus nerve stimulation; Vagus nerve stimulation therapy system